2021
DOI: 10.1039/d0ra10144c
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effect of colloidal carbon quantum dots on Bursaphelenchus xylophilus

Abstract: Bursaphelenchus xylophilus (B. xylophilus) is a dangerous plant pest which could result in Pine Wild Disease (PWD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Han et al examined the effect of CDs on the reproduction of Bursaphelenchus xylophilus , and found that a 6000 mg L −1 concentration reduced the number of eggs laid. 46 A study examining the effects of thioglycolic acid coated CdTeQDs on the reproduction of Hydra vulgaris found that exposure to CdTeQD concentrations as low as 1 mg L −1 Cd for 14 days reduced their budding rate by 42% relative to the control. 11 Another study also examined the toxicity of CdTeQDs on the reproductive performance of Drosophila melanogaster and found a dose-dependent decline in fecundity, fertility, and hatchability in the 1–100 μM (approximately 100–10 000 mg L −1 ) range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al examined the effect of CDs on the reproduction of Bursaphelenchus xylophilus , and found that a 6000 mg L −1 concentration reduced the number of eggs laid. 46 A study examining the effects of thioglycolic acid coated CdTeQDs on the reproduction of Hydra vulgaris found that exposure to CdTeQD concentrations as low as 1 mg L −1 Cd for 14 days reduced their budding rate by 42% relative to the control. 11 Another study also examined the toxicity of CdTeQDs on the reproductive performance of Drosophila melanogaster and found a dose-dependent decline in fecundity, fertility, and hatchability in the 1–100 μM (approximately 100–10 000 mg L −1 ) range.…”
Section: Resultsmentioning
confidence: 99%
“…42 Similarly, Han et al showed a decline in the number of thrashes per minute of Bursaphelenchus xylophilus in the 4000–6000 mg L −1 CD range. 46 Paithankar et al exposed Drosophila melanogaster to CdTeQDs in the concentration range of 0.2–100 μM (approximately 20–10 000 mg L −1 ) and saw no significant difference in the climbing ability of flies when compared to the control. 47 Although the literature sometimes reports that CDs and CdTeQDs can negatively impact the locomotion or climbing ability of organisms, these effects were typically observed at concentrations higher than those used in our study.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, CQDs have generated considerable interest in recent years due to their unique physical, chemical, optical, and surface features. As a carbon-based material, CQDs are abundant, inexpensive, possess unique electron transfer characteristics, and have a wide surface area, which enables CQDs to perform exceptionally well in electrochemical reactions [50][51][52][53][54]. Additionally, CQDs have extremely adjustable electrical and photoluminescence capabilities due to the quantum confinement effect, with a high degree of surface functionalization adjustment efficiency.…”
Section: Carbon Quantum Dots (Cqds)mentioning
confidence: 99%